Psychological influences on distance estimation in a virtual reality environment - Takahashi, Kohske; Meilinger, Tobias; Watanabe, Katsumi; Bülthoff, Heinrich H. (Frontiers in Human Neuroscience, 2013)
Researches on embodied perception have revealed that social, psychological and physiological factors influence perception of space. While many of these influences were observed with real or highly realistic stimuli, the present work showed that even the orientation of abstract geometric objects with a non-realistic virtual environment could influence distance perception. Observers wore a head mounted display and watched virtual cones moving within an invisible cube for five seconds with their head movement recorded. Subsequently, observers estimated the distance to the cones or evaluated their friendliness. The cones either faced the observer, a target behind the cones, or random orientations. Average viewing distance to the cones varied between 1.2 and 2.0 m. At a viewing distance of 1.6 m, observers perceived cones facing them as closer than cones facing an opposite target or random orientations. Furthermore, irrespective of viewing distance, observers moved their head away from the cones more strongly and evaluated the cones as less friendly when the cones were facing observers. Similar results of distance estimation were obtained with a 3D projection onto a large screen, although the effective viewing distance was farther away. These results suggest that factors other than physical distance could influence distance perception even with non-realistic geometric objects within a virtual environment. Furthermore, the modulation of distance perception was also accompanied by changes in subjective impression and avoidance movement. We propose that cones facing an observer are perceived as socially discomforting or threatening and potentially violate an observer’s personal space, which might influence the perceived distance of cones.